The protective effect of iron isomaltoside on myocardial ischemia-reperfusion injury via the suppression of KLF4/NF-κB signaling - Huiping Gong; Qingyang Zhao; Jingbo Zhang; Duanchen Sun; Xianghua Zhuang; Qiaofeng Dong; Aixia Dou (PLoS ONE, 2025)
This study aimed to investigate the beneficial effects of iron isomaltoside (IIM) on myocardial function and the associated mechanisms in rats with myocardial ischemia/reperfusion (I/R)-induced damage and hypoxia/reoxygenation (H/R)-induced H9C2 cells. Changes in cardiac pathology after myocardial infarction (MI) were analyzed with hematoxylin-eosin staining. Myocardial cell apoptosis in the heart tissues of rats with MI was assessed using TUNEL staining. In H/R-induced H9C2 cells, cell viability and lactate dehydrogenase (LDH) and adenosine 5’-triphosphate levels were detected. Apoptosis and MMP in H9C2 cells were detected with flow cytometry. Our results demonstrated that IIM treatment reduced myocardial injury induced by ischemia-reperfusion (I/R) and suppressed cardiomyocyte apoptosis, inflammation, and autophagy induced by I/R in rats. Moreover, we confirmed that IIM repressed apoptosis and regulated MMP in H9C2 cells exposed to H/R. IIM relieved the inflammatory response and autophagy in H/R-treated H9C2 cells. In addition, IIM inhibited the Krüpple-like factor 4 (KLF4)/NF-κB pathway in H/R-induced H9C2 cells. Interestingly, the function of IIM on apoptosis, MMP, inflammation and autophagy were abolished by KLF4 overexpression in H/R-induced H9C2 cells. In conclusion, IIM could repress cardiomyocyte apoptosis, inflammation and autophagy through the inhibition of the KLF4/NF-κB pathway and thus reduced myocardial injury in vivo and in vitro.